Differentiation from First Principles

Differentiation from First Principles

A LevelAQAEdexcelOCRAQA 2022Edexcel 2022

Differentiation from First Principles

The First Principles technique is something of a brute-force method for calculating a derivative – the technique explains how the idea of differentiation first came to being.

A Level AQA Edexcel OCR

Finding Derivatives from First Principles

To differentiate from first principles, use the formula

f'(\textcolor{blue}{x}) = \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{f(\textcolor{blue}{x} + \textcolor{purple}{h}) - f(\textcolor{blue}{x})}{\textcolor{purple}{h}} \right)

While this might look a little intimidating, it’s pretty easy to understand.

Think about how we describe the gradient between two points for a moment…

f'(\textcolor{blue}{x}) = \dfrac{d\textcolor{limegreen}{y}}{d\textcolor{blue}{x}} = \dfrac{\text{change in }\textcolor{limegreen}{y}}{\text{change in }\textcolor{blue}{x}}

Well, we can describe a “change in \textcolor{limegreen}{y}” as f(\textcolor{blue}{x} + \textcolor{purple}{h}) - f(\textcolor{blue}{x}) and a “change in \textcolor{blue}{x}” as the corresponding \textcolor{blue}{x} + \textcolor{purple}{h} - \textcolor{blue}{x} = \textcolor{purple}{h}

Surely then, as \textcolor{purple}{h} decreases toward 0, we find that the value of the gradient tends toward the actual value, f'(\textcolor{blue}{x}).

For example, the graph on the right shows the graph \textcolor{limegreen}{y}=\textcolor{blue}{x}^2. It also introduces four “chords”, each indicating the gradient between two points on the graph. As the colour transitions from green to purple, the value of \textcolor{purple}{h} is decreasing towards 0, for the point (\textcolor{blue}{1},\textcolor{limegreen}{1}).

h=2 gives f'(x)=4

h=1 gives f'(x)=3

h=0.5 gives f'(x)=2.5

h=0.1 gives f'(x)=2.1

A LevelAQAEdexcelOCR
A Level AQA Edexcel OCR

Example 1: Using the First Principles Technique

Let f(\textcolor{blue}{x}) = 3\textcolor{blue}{x}^4. By differentiating from first principles and using the binomial expansion, find f'(\textcolor{blue}{x}).

[4 marks]

f'(x) = \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{f(\textcolor{blue}{x} + \textcolor{purple}{h}) - f(\textcolor{blue}{x})}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{3(\textcolor{blue}{x} + \textcolor{purple}{h})^4 - 3\textcolor{blue}{x}^4}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{3(\textcolor{blue}{x}^{4} + 4\textcolor{blue}{x}^{3}\textcolor{purple}{h} + 6\textcolor{blue}{x}^{2}\textcolor{purple}{h}^{2} + 4\textcolor{blue}{x}\textcolor{purple}{h}^{3} + \textcolor{purple}{h}^{4}) - 3\textcolor{blue}{x}^4}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{3\textcolor{blue}{x}^{4} + 12\textcolor{blue}{x}^{3}\textcolor{purple}{h} + 18\textcolor{blue}{x}^{2}\textcolor{purple}{h}^{2} + 12\textcolor{blue}{x}\textcolor{purple}{h}^{3} + 3\textcolor{purple}{h}^{4} - 3\textcolor{blue}{x}^4}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{12\textcolor{blue}{x}^{3}\textcolor{purple}{h} + 18\textcolor{blue}{x}^{2}\textcolor{purple}{h}^{2} + 12\textcolor{blue}{x}\textcolor{purple}{h}^{3} + 3\textcolor{purple}{h}^{4}}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( 12\textcolor{blue}{x}^{3} + 18\textcolor{blue}{x}^{2}\textcolor{purple}{h} + 12\textcolor{blue}{x}\textcolor{purple}{h}^{2} + 3\textcolor{purple}{h}^{3} \right)

 

= 12\textcolor{blue}{x}^3

A LevelAQAEdexcelOCR

Example 2: Using the First Principles Technique (Again)

Let f(\textcolor{blue}{x}) = (\textcolor{blue}{x} - 1)^2 + 4\textcolor{blue}{x} - 10. By differentiating from first principles, find f'(\textcolor{blue}{x}).

[4 marks]

f(\textcolor{blue}{x}) = (\textcolor{blue}{x} - 1)^2 + 4\textcolor{blue}{x} - 10 = \textcolor{blue}{x}^2 + 2\textcolor{blue}{x} - 9

 

f'(\textcolor{blue}{x}) = \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{f(\textcolor{blue}{x} + \textcolor{purple}{h}) - f(\textcolor{blue}{x})}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{(\textcolor{blue}{x} + \textcolor{purple}{h})^2 + 2(\textcolor{blue}{x} + \textcolor{purple}{h}) - 9 - \textcolor{blue}{x}^2 - 2\textcolor{blue}{x} + 9}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{\textcolor{blue}{x}^2 + 2\textcolor{purple}{h}\textcolor{blue}{x} + \textcolor{purple}{h}^2 + 2\textcolor{blue}{x} + 2\textcolor{purple}{h} - 9 - \textcolor{blue}{x}^2 - 2\textcolor{blue}{x} + 9}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( \dfrac{2\textcolor{purple}{h}\textcolor{blue}{x} + \textcolor{purple}{h}^2 + 2\textcolor{purple}{h}}{\textcolor{purple}{h}} \right)

 

= \lim\limits_{\textcolor{purple}{h} \to 0} \left( 2\textcolor{blue}{x} + \textcolor{purple}{h} + 2 \right)

 

= 2\textcolor{blue}{x} + 2

A LevelAQAEdexcelOCR

Example Questions

f'(x) = \lim\limits_{h \to 0} \left( \dfrac{f(x + h) - f(x)}{h} \right)

 

= \lim\limits_{h \to 0} \left( \dfrac{x + h - x}{h} \right)

 

= \lim\limits_{h \to 0} \left( \dfrac{h}{h} \right) = \lim\limits_{h \to 0} 1 = 1, for all h and all x.

\dfrac{dy}{dx} = \lim\limits_{h \to 0} \left( \dfrac{c - c}{h} \right)

 

= \lim\limits_{h \to 0} \left( \dfrac{0}{h} \right)

 

= \lim\limits_{h \to 0} \left( 0 \right)

 

= 0
f(x) = (1 + x^2)^2 = 1 + 2x^2 + x^4

gives

f'(x) = \lim\limits_{h \to 0} \left( \dfrac{1 + 2(x + h)^2 + (x + h)^4 - 1 - 2x^2 - x^4}{h} \right)

 

= \lim\limits_{h \to 0} \left( \dfrac{1 + 2(x^2 + 2xh + h^2) + (x^4 + 4x^{3}h + 6x^{2}h^{2} + 4xh^{3} + h^{4}) - 1 - 2x^2 - x^4}{h} \right)

 

= \lim\limits_{h \to 0} \left( \dfrac{1 + 2x^2 + 4xh + 2h^2 + x^4 + 4x^{3}h + 6x^{2}h^{2} + 4xh^{3} + h^{4} - 1 - 2x^2 - x^4}{h} \right)

 

= \lim\limits_{h \to 0} \left( \dfrac{4xh + 2h^2 + 4x^{3}h + 6x^{2}h^{2} + 4xh^{3} + h^{4}}{h} \right)

 

= \lim\limits_{h \to 0} \left( 4x + 2h + 4x^{3} + 6x^{2}h + 4xh^{2} + h^{3} \right)

 

= 4x + 4x^{3}

Additional Resources

MME

Exam Tips Cheat Sheet

A Level
MME

Formula Booklet

A Level

You May Also Like...

A Level Maths Revision Cards

The best A level maths revision cards for AQA, Edexcel, OCR, MEI and WJEC. Maths Made Easy is here to help you prepare effectively for your A Level maths exams.

£14.99
View Product

A Level Maths – Cards & Paper Bundle

A level maths revision cards and exam papers for Edexcel. Includes 2022 predicted papers based on the advance information released in February 2022! MME is here to help you study from home with our revision cards and practise papers.

From: £22.99
View Product

Transition Maths Cards

The transition maths cards are a perfect way to cover the higher level topics from GCSE whilst being introduced to new A level maths topics to help you prepare for year 12. Your ideal guide to getting started with A level maths!

£8.99
View Product